Coronary Artery Bypass Grafting Surgery Off- or On-pump Revascularisation Study (CORONARY): kidney substudy analytic protocol of an international randomised controlled trial. Issue 2 (18th April 2012) - Garg, Amit X; Devereaux, P J; Yusuf, Salim; Cuerden, Meaghan S; Parikh, Chirag R; Coca, Steven G; Walsh, Michael; Cook, Richard J; Whitlock, Richard P; Noiseux, Nicolas; Novick, Richard J; Ou, Yongning; et al.
Abstract : Introduction: CORONARY is a large international randomised controlled trial comparing coronary artery bypass graft (CABG) surgery done with and without a bypass pump. Compared with on-pump, off-pump surgery may prevent acute kidney injury (AKI) in the short term and may better preserve kidney function 1 year following surgery. Secondary analyses may also clarify whether effects are similar in patients with and without pre-operative chronic kidney disease and whether AKI avoidance mediates preserved 1-year kidney function. Methods and analysis: With respect to the study schedule, the last of 4752 patients from 79 sites in 19 countries were randomised in November 2011 to cardiac surgery performed with an on-pump or off-pump procedure. The authors will use regression models to compare the groups in the outcome of peri-operative AKI (per cent change in serum creatinine, ≥50% increase in serum creatinine) and 1-year kidney function (per cent change in estimated glomerular filtration rate (eGFR), ≥20% eGFR loss 1 year after surgery). The authors will use interaction terms in regression models to determine if there is a differential impact of the intervention in those with and without pre-existing chronic kidney disease. The authors will use regression-based tests to determine the proportion of the total effect of surgery type (off-pump vs on-pump CABG) on 1-year eGFR that is mediated by peri-operative AKI. Ethics and dissemination: In the year 2009, the authors were competitively awarded a grant from the Canadian Institutes of Health Research to answer these kidney questions in CORONARY. Ethics approval was obtained for additional renal data collection in centres that agreed to study participation (>90% of participating centres). This collection began for patients enrolled after 1 January 2010. Remaining 1-year renal outcome data will be collected throughout 2012. Results will be reported in 2013. Clinical trial registration number: NCT 00463294.